The role of microRNAs in the pathogenesis of thyroid cancer - Ghafouri-Fard, Soudeh (Noncoding RNA Res, 2020)
Thyroid cancer is the most frequent type of cancers originating from the endocrine system. Early diagnosis leads to good clinical outcome in differentiated types of thyroid cancer. Yet, there are few treatment options for patients with medullary or anaplastic thyroid cancer. Thus, identification of molecular markers that explain the pathologic process during evolution of this cancer has practical significance. MicroRNAs (miRNAs) have been shown to influence the activity of thyroid cancer-related signaling pathways such as MAPK pathway and RET gene. These small transcripts not only can differentiate malignant tissues from non-malignant tissues, but also have differential expression in different stages of thyroid cancer. Assessment of serum levels of miRNAs is a practical noninvasive method for follow-up of patients after thyroidectomy. Moreover, the therapeutic effects of a number of miRNAs have been verified in xenograft models of thyroid cancer. In the current review, we summarize the data regarding the role of miRNAs in thyroid cancer.